Home Healthcare Workers' Occupational Exposures. (September 2020) - Bien, Elizabeth; Davis, Kermit; Gillespie, Gordon
Abstract : Home healthcare workers (HHCWs) belong to one of the fastest growing industries and have an unpredictable work environment, potentiating their risk of exposures to occupational hazards. More patients seeking care for chronic health conditions, and improvements in technology and medical advancements are allowing more complex patient care to be provided at home. A comprehensive integrative review was completed, identifying nine articles that provide an overview of the occupational hazards HHCWs face. Analysis of the articles indicates occupational hazards are similar across studies. Occupational exposures reported by HHCWs align within all the studies and include exposures to blood, saliva, dangerous conditions walking to and within the home, secondhand smoke, aggressive pets, violence, and ergonomic concerns. These studies have been methodologically limited to self-reports, including surveys, interviews, and focus groups but include quantitative and qualitative data. Future research can further describe and identify specific occupational exposures and health hazards, subsequently leading to modifications to protect the health and safety of HHCWs, personal care workers, and the informal caregivers who provide care in the home.